Study on the influence of metallic powder in near-dry electric discharge machining - Sundriyal, Sanjay (Strojniški vestnik, 2020)
Near-dry electrical discharge machining (ND-EDM) is an eco-friendly process. In this study, an approach has been made to make the machining process more efficient than ND-EDM with the addition of metallic powder with the dielectric medium to machine EN-31 die steel. Powdermixed near-dry EDM (PMND-EDM) has several advantages over the ND-EDM or conventional electrical discharge machining (EDM) process, such as a higher material removal rate (MRR), fine surface finish (Ra), sharp cutting edge, lesser recast layer, and lower deposition of debris. The output response variables are MRR, Ra, residual stress (RS) and micro-hardness (MH) of the machined surfaces. Further study of the workpiece was performed, and a comparative study was conducted between ND-EDM and PMND-EDM. In this proposed method of machining, the MRR, Ra, and MH increased by 17.85 %, 16.36 %, and 62.69 % while RS was reduced by 56.09 %.
Keywords: material removal rate; near-dry EDM; površinska hrapavost; powder mixed near-dry EDM; preostale napetosti; residual stress; skoraj suha elektroerozijska obdelava; skoraj suha elektroerozijska obdelava s primešanim prahom; stopnja odvzema materiala; surface roughness